DESEMPENHO MOTOR DE PRATICANTES DE GINÁSTICA RÍTMICA: UM OLHAR CENTRADO NAS CARACTERÍSTICAS FÍSICAS E MATURACIONAIS - Adenizia Luciana Julião (2022)
Introduction: The performance of gymnasts can be observed in different ways, since it depends on a number of factors, including maturational factors, physical type and level of physical conditioning. Objective: To describe and associate physical, maturational and training characteristics with the motor performance of rhythmic gymnastics practitioners. Design and methods: This is a cross-sectional, observational, descriptive study with quantitative analysis. The non-probabilistic conventional sample consisted of 102 female Rhythmic Gymnastics practitioners, aged between 9 and 16 years, from two training centers in the city of Campo Grande - MS. Based on the median of the overall physical fitness score, the sample was divided into two groups: lower performance group (GMED; below the median) and higher performance group (GMAD; above the median). Data collection was carried out through the application of questionnaires with parents and gymnasts, in order to obtain data on menarche and information on training, in addition to carrying out anthropometric and body composition assessments, general and specific motor performance tests for evaluation flexibility, balance, strength, power and endurance. Results: It was found that GMAD gymnasts train significantly more hours, are older, have a greater number of practitioners who have already gone through menarche (n=28; 54.9%) and higher values of skeletal muscle mass (17.84± 4.47kg). In addition, they have significantly lower mean values of fat percentage (20.5±6.65%), BMI (18.63±2.60kg/m²), arm circumference (23.99±2.61cm), triceps, subscapularis and supraspinatus (12.58±4.74mm; 9.45±4.48mm; 9.88±6.97mm, respectively), when compared to gymnasts from the GMED group. In the somatotype classification, the groups have distinct somatotypes, central GMAD (3.6-3.8-3.2), and mesoendomorph GMED (5.02-4.13-2.89). The GMAD gymnasts had better performance in all motor tests performed. Having as explanatory variables of performance in 55.8% (R²= 0.558), endomorphy and menarche occurrence Final considerations: it is concluded that the greater the endomorphy, the lower the chance of the gymnast belonging to the group with the best performance in RG. Finally, the assessment of motor performance in RG practitioners is of fundamental importance for coaches and guardians who deal with the preparation of athletes and the understanding of how aspects of body composition and maturation influence motor performance. Keywords: Rhythmic Gymnastics; Flexibility; Biological Maturation; Somatotype; Physical Growth.